2017
DOI: 10.3390/su9112131
|View full text |Cite
|
Sign up to set email alerts
|

Waterlogging in Arid Agriculture Areas Due to Improper Groundwater Management—An Example from Kuwait

Abstract: Abstract:Waterlogging is an acute problem in the agricultural areas of arid regions. This study highlights the main reasons for water table rise in the Wafra agriculture area of South Kuwait. A two-tier aquifer system exists in the area, which consists of the Kuwait Group aquifer underlain by a semi-confined Dammam aquifer. Improper sealing of wells tapping the semi-confined Dammam aquifer and over-irrigation were the main reasons for water level rise, and an increase in total dissolved solids was due to high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Approximately 10%-13% of Kuwait's total groundwater production is blended with desalinated distilled water to make it potable. Groundwater is used for various purposes in Kuwait, including irrigation, gardening, construction, and even animal watering (Al-Murad et al, 2017). Currently, this water system satisfies the demand for water for more than 75,000 consumers at a considerably lower price.…”
Section: Brackish Groundwatermentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 10%-13% of Kuwait's total groundwater production is blended with desalinated distilled water to make it potable. Groundwater is used for various purposes in Kuwait, including irrigation, gardening, construction, and even animal watering (Al-Murad et al, 2017). Currently, this water system satisfies the demand for water for more than 75,000 consumers at a considerably lower price.…”
Section: Brackish Groundwatermentioning
confidence: 99%
“…The agricultural areas are in three significant directions and have approximately 2,880 farms with 141 million m 2 . However, 90% of Kuwait's land is considered unsuitable for agricultural purposes, where main crop productions include vegetables, potatoes, and grains (Al-Murad et al, 2017). There are three main sources of water in Kuwait for agricultural utilization: brackish groundwater, treated wastewater, and desalinated water.…”
Section: Water Demand and Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…9). This problem is caused by the topographic nature of the study area due to the high ground elevations in the west, the poor drainage of the soil and the use of flood irrigation systems (Gad, 2004), in addition to the increased aquitard (soil) thickness as well as the shallow water table . The excessive usage of water in irrigation leads to waterlogging and finally soil salinization (Al-Murad et al, 2017). Other factors such as soil thickness (Houk et al, 2005(Houk et al, , 2006, soil type, geology and geomorphology play important role in the occurrence of waterlogging and salinization problems in agricultural area (Hatton et al, 2002;McFarlane and Williamson, 2002;Holden et al, 2006).…”
Section: Waterlogging Phenomenamentioning
confidence: 99%
“…It has been suggested in several previous studies that the development of antibiotic resistance by bacteria was due to the occurrence of subtherapeutic concentrations of these antibiotics in these environments [53,54]. Several studies have reported measurable concentrations of antibiotics in the WWTP effluents that eventually ended up in surface waters [55][56][57][58] or even in the food chain [59] following recent and frequent applications of treated wastewater in aquaculture and agriculture [60]. There are many studies on antibiotics released from WWTPs in Europe [61,62], North America, the East, and the Far East [63,64], but very few assessments have been carried out in the Middle East and Africa [11,[65][66][67].…”
Section: Introductionmentioning
confidence: 99%